Hubungan Diabetes Mellitus dan Non-Diabetes Mellitus Dengan Survival Rate Pasien Gagal Ginjal Kronik Yang Manjalani Hemodialisis di RSUDZA Banda Aceh Periode 2011-2015 - Nurul Fitria; Maimun Syukri; Juwita Saragih (Jurnal Ilmiah Mahasiswa Kedokteran Medisia, 2017)
Chronic renal failure is a global health problem that is important to be noted because its prevalence continues to increase rapidly. Patient with chronic renal failure require renal replacement therapy in order to maintain their life (survival rate), one of the renal replacement therapies is hemodialysis. The Causes of chronic renal failure such as diabetes mellitus and non-diabetes mellitus are important factory associated with survival rate of patients undergo hemodialysis therapy. The aims of this study is to determine the relationship between diabetes mellitus and non-diabetes mellitus with the survival rate of chronic renal failure patients who undergo hemodialysis therapy. This  study was an analytical observational study with cross sectional design approach. Data were obtained from medical records of patient who undergo hemodialysis therapy in Banda Aceh RSUDZA period 2011-2015. The samples were taken by using total sampling with total of respondents are 92 people. Data were analyzed using chi-square or if not fulfilled the requirements, then it will be tested with Fisher’s Exact Test. Statistically the result of chi-square test with alternative test Fisher’s Ecaxt Test showed that the p value=0,000 (0,05).